WYDANIE LISTU ŻELAZNEGO JAKO REZULTAT PERTRAKTACJI PROCESOWYCH - Struczyk, Edward (Zeszyty Prawnicze, 2017)
The Safe - conduct Decision Issue as a Result of the Proceedings Negotiation Summary The article presents the normative structure of the safe-conduct perceived as a way to enter into a contract between the defendant and a competent district court. In principle, the settlement prevents the defendant from being arrested. But on the other hand the safe-conduct benefits the administration of justice by making it possible to initiate penal proceedings against such a defendant. The mutual advantages bought by the safe-conduct decision allow us to treat the preceding procedure as a phase of the proceedings negotiation.